2007
DOI: 10.1029/2006wr005659
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soil stratification on the development and migration of headcuts in upland concentrated flows

Abstract: [1] Experiments were conducted to examine the effect of vertical stratification in soil erodibility on the development and migration of steady state headcut scour holes in upland concentrated flows typical of agricultural fields. Packed soil beds with a preformed step were subjected to identical simulated rainstorms and clear-water overland flow rates, which resulted in predictable, actively migrating headcut scour holes with nearly identical characteristics. When an erosion-resistant layer was incorporated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 30 publications
4
29
0
Order By: Relevance
“…Accordingly, gully soil erodibility, and in particular its critical shear stress and erodibility coefficient, would be affected by such weathering processes (Knapen et al 2007). Previous studies (Alonso et al 2002;Gordon et al 2007;Hanson et al 2001) have also shown that headcuts migrate upstream due to hydraulic stress at the overfall, weathering processes, and seepage at the base of headcuts as well as gravitational forces on soil mass. Therefore, these weathering processes would result in obvious changes to gully erosion processes.…”
Section: Discussionmentioning
confidence: 92%
“…Accordingly, gully soil erodibility, and in particular its critical shear stress and erodibility coefficient, would be affected by such weathering processes (Knapen et al 2007). Previous studies (Alonso et al 2002;Gordon et al 2007;Hanson et al 2001) have also shown that headcuts migrate upstream due to hydraulic stress at the overfall, weathering processes, and seepage at the base of headcuts as well as gravitational forces on soil mass. Therefore, these weathering processes would result in obvious changes to gully erosion processes.…”
Section: Discussionmentioning
confidence: 92%
“…This trend was caused by the high flow discharge generating more overland flow, which then influenced the flow hydraulic characteristics by increasing the local turbulence (Guy, Dickinson, & Rudra, 1987). On the one hand, the increasing flow discharge increased the depth of the scour hole on the gully head, thus increasing the collapse frequency of the overhanging layers of the gully heads (Chen et al, 2013;Gordon, Bennett, Wells, & Alonso, 2007) and increasing the undercut sediment. The runoff that dropped from the border of the catchment area was divided into the wall pressing flow and the jet flow (Flores-Cervantes, Istanbulluoglu, & Bras, 2006).…”
Section: Sediment Characteristics Of Headcut Erosionmentioning
confidence: 99%
“…The experimental facility utilized packed soil beds, applied rainfall and overland fl ow, and a pre-formed step to trigger headcut development. The following observations were made (refer to Bennett, 1999;Bennett et al, 2000a;Bennett and Casalí, 2001;Gordon et al, 2007b): (1) After an initial period of bed adjustment, steady-state soil erosion conditions were observed where a scour hole (headcut) migrated upstream at a constant rate, its scour depth S D (the vertical distance from the brinkpoint to the maximum scour depth) and scour length S L (the horizontal distance from the brinkpoint to the maximum scour depth) remained nearly invariant with distance, and the sediment discharge Q s exiting the fl ume remained nearly invariant with time. (2) Larger, steady-state headcut scour holes with higher sediment discharges were observed for higher overland fl ow rates, higher bed slopes, and larger initial step heights.…”
Section: Introductionmentioning
confidence: 99%